Principles of Microeconomics - Taylor, Timothy; Greenlaw, Steven A.; Dodge, Eric (Open textbook library., 2014)
Principles of Economics 2e covers the scope and sequence of most introductory economics courses. The text includes many current examples, which are handled in a politically equitable way. The outcome is a balanced approach to the theory and application of economics concepts. The second edition has been thoroughly revised to increase clarity, update data and current event impacts, and incorporate the feedback from many reviewers and adopters. Changes made in Principles of Economics 2e are described in the preface and the transition guide to help instructors transition to the second edition. The first edition of Principles of Economics by OpenStax is available in web view in the ancillaries